Olfactory dysfunction as a diagnostic and prognostic marker for movement disorders - Aliasghar Peyvandi; Shahrokh Khoshsirat; Narges Bazgir; Amirreza Zaker; Azin Tahvildari; Somayeh Niknazar; Sara Mohammadi; Mehri Salari (Annals of Movement Disorders)
Olfactory dysfunction (OD) is a common nonmotor symptom observed in several movement disorders. The severity and pattern of olfactory impairment vary among these conditions. Notably, olfactory impairment often precedes the clinical diagnosis of movement disorders by several years, yet it remains frequently unrecognized by patients and physicians until formal olfactory tests are undertaken. This review focuses on exploring OD across various movement disorders. A systemic search strategy incorporating key terms such as movement disorders, dystonic disorders, tic disorders, parkinsonian disorders, parkinsonism, ataxia, essential tremors, drug-induced akathisia, and olfaction disorders was employed to query databases including Embase, Scopus, and PubMed. After excluding irrelevant articles, 99 studies were selected for comprehensive review. OD is a persistent feature across all movement disorders, with the exception of pseudo supranuclear palsy. Among these conditions, olfactory impairment is much more frequent and severe in patients with Parkinson’s disease. Incorporating olfactory testing into the diagnostic evaluation of at-risk individuals or patients with established movement disorders is recommended. These olfactory tests offer a practical, cost-effective, and convenient diagnostic tool that may aid in the early identification and management of these conditions.